Lipase-catalyzed interfacial polymerization of ω-pentadecalactone in aqueous biphasic medium: A mechanistic study - Pabhangkon Panlawan (2018)
The synthetic activity of lipases in biphasic o/w systems was investigated with respect to their use in the synthesis of polyester chains via transesterification reactions. Lipase-catalyzed ring-opening polymerization (ROP) of pentadecalactone (ω-PDL) dispersed in water was used as a model reaction to understand the synthetic activity of lipases in biphasic o/w system. We conducted a systematic investigation of the influence of reaction conditions on the macromolecular characteristics of oligo(ω-PDL) encompassing chemical, thermophysical and colloidal properties of the reaction medium. A model was proposed assuming Michaelis-Menten interfacial kinetics followed by chain extension via lipase-catalyzed linear polycondensation. The solidification of oligo(ω-PDL) chains with a degree of polymerization of approximately three was identified as a major factor limiting the molecular weight of obtained oligomers to ∼870 g mol-1, despite the fast reaction rate and complete conversion of ω-PDL. The addition of toluene into the dispersed phase at a volumetric ratio of 0.3-0.5 of toluene to ω-PDL allowed us to circumvent this problem and increase the molecular weight of obtained oligomers up to 1460 g mol-1. The molecular weight of polymer product according to this model was thus inversely related to the weight ratio percentage of interfacial lipase PS to ω-PDL per droplet and correspondingly correlated with the activity of lipase. Taking into account all these parameters allowed increasing the molar mass of oligo(ω-PDL) from 870 g mol-1to 3507 g mol-1. © 2012 Elsevier B.V.